2018
DOI: 10.5038/2640-6489.3.1.1029
|View full text |Cite
|
Sign up to set email alerts
|

Reinventing tourism cities: Examining technologies, applications, and city branding in leading smart cities

Abstract: Cities have become the engines of economic development more than ever before. Nowadays, numerous cities have been using technological and innovative service delivery tools called "smart city technologies and applications" to affect living conditions of their residents and visitors positively. These technologies and applications can be seen at government and private buildings, city facilities and management, informational and communicational technology infrastructure and personal services. They have a net-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…There needs to be a lot of progress to create smart transportation initiatives in Turkish cities and it seems that the major problems faced by the cities in adoption of smart systems are lack of quality public transportation, road safety concerns, poor traffic management, lack of modal options and funding, and poor public transportation [103]. Although, a range of civil society activities was recently set up to energize planning, transport, and environmental authorities to develop strategies to promote smart systems, including The CityFix Turkiye, EkoIQ, Wrisehirler, and Embarqturkiye [104][105][106][107][108][109][110], there is still a small body of projects that are concerned with smart transport applications in Turkey [111]. In addition, a few good smart approaches, advances, and applications have been made in current practice, and these initiatives have been implemented by the central government, with public engagement being excluded from evidence, knowledge, debate, and the policy-making developments [112,113].…”
Section: Smart Transportation Approaches Advances and Applicationsmentioning
confidence: 99%
“…There needs to be a lot of progress to create smart transportation initiatives in Turkish cities and it seems that the major problems faced by the cities in adoption of smart systems are lack of quality public transportation, road safety concerns, poor traffic management, lack of modal options and funding, and poor public transportation [103]. Although, a range of civil society activities was recently set up to energize planning, transport, and environmental authorities to develop strategies to promote smart systems, including The CityFix Turkiye, EkoIQ, Wrisehirler, and Embarqturkiye [104][105][106][107][108][109][110], there is still a small body of projects that are concerned with smart transport applications in Turkey [111]. In addition, a few good smart approaches, advances, and applications have been made in current practice, and these initiatives have been implemented by the central government, with public engagement being excluded from evidence, knowledge, debate, and the policy-making developments [112,113].…”
Section: Smart Transportation Approaches Advances and Applicationsmentioning
confidence: 99%
“…Additionally, in several studies, deficiency in coordination among non-governmental organizations and lack of communication and coordination among stakeholders has been concluded (Akça, 2006;Durgun, 2007;Genç et al, 2014;Hatipoğlu et al, 2016;Zengingönül et al, 2012). Yavuz et al (2018) suggested that tangible and intangible qualities of a city could be dispersed to its target audiences by collaborating with stakeholders. Recently, Wondirad et al (2020) paid attention to poor governance and poor-stakeholder collaboration which are ranked among the top factors responsible for the devastation of ecotourism resources in Southern Ethiopia.…”
Section: Lack Of Coordination and Cooperationmentioning
confidence: 99%
“…Teknologi dan aplikasi merupakan sebuah kewajiban infrastukrur teknologi informasi dan komunikas. Kota-kota telah menggunakan teknologi dan aplikasi ini untuk mencap diri mereka sebagai ekonomi yang efisien, berkelanjutan, dan kuat, keamanan, kerapihan, perencanaan fasilitas kota, citra sipil yang disempurnakan, dan kualitas hidup yang tinggi (Yavuz et al, 2018).…”
Section: Brandingunclassified